2019
DOI: 10.1186/s12863-019-0760-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic transcriptome profile of sheep (Ovis aries) in response to overgrazing: novel genes and pathways revealed

Abstract: Background Overgrazing is a major factor that causes steppe degradation in Inner Mongolian, resulting in extensive ecosystem damage. Scarcity of grass means sheep are smaller and therefore mutton and cashmere production is greatly reduced, which has resulted in massive annual economic losses. Liver is the primary metabolic organ in mammals. It is also the key source of energy supply and detoxification of metabolites in animals, has a close relationship with animal growth. However, investigations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…High-throughput methods have been widely applied to understand both the physiological and pathological characteristics in the liver of various species [12][13][14]. In this study, we compared the liver transcriptomes between IUGR and normal neonatal piglets from Day 1 to Day 7, to the weaning day (Day 28) using whole-genome transcriptional sequencing, to gain insight into the dynamics of metabolism, growth, and development in IUGR piglets.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput methods have been widely applied to understand both the physiological and pathological characteristics in the liver of various species [12][13][14]. In this study, we compared the liver transcriptomes between IUGR and normal neonatal piglets from Day 1 to Day 7, to the weaning day (Day 28) using whole-genome transcriptional sequencing, to gain insight into the dynamics of metabolism, growth, and development in IUGR piglets.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that GSTM3 and GSTK1 contributed to oxidative stressā€“mediated liver damage ( Uno et al, 2020 ). We observed that down-regulation of GSTM3 and GSTK1 expression in the liver of cold season grazing yaks, which may be due to shortage of forage and low temperature in the cold season, induced excessive physical activity and negative nutrient balance, thereby inducing oxidative stress and immune response ( Ren et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These complex lipids are stored in lipid droplets or secreted into the circulation as intestinally derived chylomicrons (CMs) and very low-density lipoprotein (VLDL) particles. The genes involved in lipid synthesis were down-regulated, whereas the pathways gluconeogenesis ( Yu et al, 2016 ), fatty acid oxidation ( Yu et al, 2016 ; Ren et al, 2019 ), and peroxisome proliferator-activated receptor A (PPAR-A) target genes (involved in lipolysis) ( Laporta et al, 2014 ) were up-regulated in ruminants under nutritional deprivation. However, the recent study suggests that lipid catabolism, fatty acid synthesis, glucose intake, and fatty acid oxidation in yaks were all inhibited by regulating the AMPK (adenosine 5ā€²-monophosphate-activated protein kinase) signaling over cold seasons ( Xiong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations